1990
DOI: 10.1029/ja095ia11p18861
|View full text |Cite
|
Sign up to set email alerts
|

Vortex‐induced tearing mode instability as a source of flux transfer events

Abstract: A two‐dimensional MHD simulation is performed to investigate the evolution and the asymptotic quasi‐static state (AQSS) of the vortex‐ induced tearing mode instability (VITM) at the magnetospheric boundary. The original VITM model is extended by including By, a magnetic field component along the invariant direction, and varying N, the number density, which makes the model applicable to a wide region on the day side magnetopause. The AQSS is found to be characterized by a large‐scale magnetic island together wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 22 publications
2
20
1
Order By: Relevance
“…This result shows that the FTEs observed in the low-latitude MP are not likely to be generated by the VIR scenario. This mechanism is shown to be more effective in the mid-and high-latitudes [7,24] .…”
Section: The Possible Mechanism Of the Observed Fte Generationmentioning
confidence: 91%
See 1 more Smart Citation
“…This result shows that the FTEs observed in the low-latitude MP are not likely to be generated by the VIR scenario. This mechanism is shown to be more effective in the mid-and high-latitudes [7,24] .…”
Section: The Possible Mechanism Of the Observed Fte Generationmentioning
confidence: 91%
“…There have been many studies on observed features of FTEs (see, for example, the review by Elphic [3] ) and recent works are focusing more on the basic questions regarding their generation mechanisms. After the three widely accepted theoretical models of FTE formation, i.e., the multiple X-line reconnection (MXR) model [4] , the single X-line bursty reconnection (SXBR) model [5] and the vortex induced reconnection (VIR) model [6,7] , Raeder [8] successfully reproduced the forming process of FTEs during strong southward IMF with a global numerical simulation, showing that the FTEs are produced by the sequential generation of new X-lines, which leads to a modified form of dual or multiple X-line reconnection. Wang et al [9] investigated the dependence of Cluster FTEs on solar wind conditions between February 2001 and June 2003 and found the controlling efficiency of different IMF and solar wind parameters on the occurrence, separation time, peak-peak magnitude and dawn-dusk asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…How do the field and flow patterns of these structures vary when the sheared flows become stronger and not negligible? To find out the answer to this question we perform a two step simulation study (Pu et al, 1990b): first we run the code by setting V 0 = 0 and obtain the results similar to those shown in Figure la, then we take the obtained island and vortex as initial perturbations to run the VR code with a flow shear which increases linearly with time during 0<t<40, reaching DV at t = 40, and then stop increasing after t = 40. It is found that, as the flow shear enhances, magnetic field lines tend to be parallel to the streamlines rather quickly; meanwhile, the magnetic island and vortex gradually become concentric.…”
Section: The Evolution Of the Moving Reconnected Structurementioning
confidence: 95%
“…Continuous reconnection can be triggered at single X point, while situations become complicated for FTEs. As we know, several mechanisms such as Multiple X line Reconnection (MXR) model [Lee and Fu, 1985], Vortex-Induced Reconnection (VIR) model [Pu et al, 1990, Liu andHu, 1988], and Bursty Single X Line Reconnection (BSXR) model [Scholer, 1988], etc., have been put forward to explain the formation of FTEs. In MXR model, Lee and Fu [1986] argued that the processes in multiple X line reconnection need additional time to increase the ratio of the length of current sheet to its width to higher value than that for the triggering of single X point.…”
Section: Discussionmentioning
confidence: 99%